ANALISIS LAPORAN KEUANGAN GUNA MEMPREDIKSI KEBANGKRUTAN DENGAN MENGGUNAKAN MODEL ALTMAN Z-SCORE PADA PERUSAHAAN TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK INDONESIA ( PT XL Axiata Tbk dan PT Indosat Tbk ) - Ridwan, Putri Fitria; Hardi, Meiril (JEA17: Jurnal Ekonomi Akuntansi, 2017)
ABSTRACTThis study aims to determine the potential bankruptcy using the Altman Z-Score in the telecommunications company listed on the Indonesia Stock Exchange (BEI). Because telecommunications taking an important role in everyday life, both in terms of day-to-day telecommunications as well as in terms of business. Selected objects to do this research is PT XL Axiata Tbk and PT Indosat Tbk, which is two telecommunications company that is developing and steal the attention of consumers at the moment. The method of the research is to analyze the company's financial statements using analysis tools Altman Z-Score. Use of Altman Z-Score aims to be able to know or predict the financial condition perusahaa, because of the financial statements and the calculation of Altman Z-Score can be known, whether the company experienced financial difficulties in the future or not. Z-Score analysis model using five variables that represent liquidity ratio (X1), profitability (X2 and X3), activity (X4 and X5) and the data used are the financial statements for 2011-2013 were obtained through the site Indonesian Stock Exchange (BEI ) is www.idx.co.id. With the formulation of the Z-Score = 1.2 1.4 X1 + X2 + X3 3.3 +0.6 + 1.0 X4 X5 with the assessment criteria Z-Score> 2.99 categorized as a very healthy company, 1.81 <Z-Score <2.99 were in gray area so the chances saved and the possibility of bankruptcy. From the analysis, based on calculations that have been made to the financial statements that PT XL Axiata Tbk and PT Indosat Tbk during the period 2011-2013 experienced financial condition is said to be bankrupt due to the calculation results Z-Score PT XL Axiata Tbk in 2011 1.23, year in 2012 and 1.29 in 2013 to 0.87 while for PT Indosat Tbk in 2011 was 0.46, in 2012 and 0.47 in 2013 to 0.25. With the results of the Z-Score <1.81, which indicates that the company entered into the category bangkut or companies experiencing very serious financial difficulties. Then the company should improve financial performance by reducing the debt and increase equity by utilizing available assets. Keywords: Financial Statements, Bankruptcy and Z-score